A Suitable Shape of the Suction Head for a Cleaning Process in a Factory Developed by Computational Fluid Dynamics - Jatuporn Thongsri; Worapol Tangsopa; Jirawat Khongsin (My University, 2021)
The previous shape of the suction head (SH) employed in a cleaning process in a factory had a low performance, removed fewer particles, and generated an annoying noise. Therefore, new shapes of SH have been proposed to solve the issues and the cleaning performance was investigated by the Shear Stress Transport (SST) k-ω turbulence, Discrete Phase (DP), Large Eddy Simulation (LES), and Ffowcs Williams and Hawkings (FW–H) models in a transient state of computational fluid dynamics (CFD). The SST k-ω and DP models were applied to determine the airflow, suspension velocity, cleaning region, and particle trace. In addition, the LES and FW–H models were used to evaluate the noise, sound pressure level, and frequency generated from the proposed shapes. All simulation results were validated with the air velocity and noise measurements and were analyzed to find a suitable shape. The simulation and experimental results revealed that the shapes of the SH affected the cleaning performance and noise generation. The higher the air velocity, the higher the noise generation. The suitable shape delivered a 4.37% better particle removing performance and 11.1 dB less noise generation than the previous shape. The outcomes of this research are the suitable shape of the SH and the research methodology which enabled the application of both CFD and experiments to solve the issue to help enhance the efficiency of the cleaning process in an actual factory.
Keywords: Transient (computer programming); Particle (ecology); Aerodynamics and Acoustics in Jet Flows